Histone acetylation functions in the wound-induced spore formation in nori - Guan, Xiaowei; Qian, Huijuan; Qu, Weihua; Shu, Shanshan; Pang, Ying; Chen, Nianci; Zhang, Xiaoqian; Mao, Yunxiang; Poestch, Ansgar; Wang, Dongmei (Frontiers in Plant Science, 2022)
The red macroalgae Neopyropia yezoensis is one of the most economically important marine crops. In the asexual reproduction process, released archeospores could provide secondary seedling resources in nori farming and be used to establish asexual seeding strategies. We previously found that wounds could induce the somatic cells in sectioned Neopyropia thalli to develop into large number of asexual spores in a short time. Many genes involved in signaling pathways, cell division, cell wall remodeling, etc. exhibited transcriptional variation in this cell fate transition process. However, the regulatory mechanisms controlling gene transcription remain elusive. In this study, we found that SAHA, the inhibitor of histone deacetylase, strongly repressed the formation of asexual spores after wounding. The lack of a sharp increase in HDAC activity after wounding was observed in SAHA-treated thalli fragments, thus confirming a histone deacetylation-related epigenetic mechanism of wound-induced cell fate reprogramming. Moreover, histone deacetylation is required in the whole process of wound-induced spore formation and release. We further compared the genome-wide transcriptional variations after SAHA treatment. 291 candidate genes were identified, including some transcriptional factors, chromatin remodeling complex proteins, protein kinases, etc. Transcription of RBOH genes was also altered by SAHA, and moreover, ROS signals in cut fragments were attenuated, both indicating that the ROS systematic signaling pathway is one of the essential targets of histone deacetylation. Our findings provide insights into the biological significance of dynamic histone acetylation states in the formation of wound-induced spores in N. yezoensis.